Influence of palm oil fuel ash on fresh and mechanical properties of selfcompacting concrete - Mohammadhosseini, Hossein; Abdul Awal, A S M; Ehsan, Abdul Haq (Indian Academy of Sciences, 2015)
This paper presents experimental results of some fresh and hardened state properties of selfcompacting concrete (SCC) incorporating palm oil fuel ash (POFA). Three concrete mixes namely ordinary Portland cement (OPC) concrete i.e. concrete with 100% OPC as control, and concrete with 30% and 60% POFA having different water/binder (w/b) ratios of 0.4, 0.45 and 0.5 were prepared. Filling ability, passing ability and segregation resistance of SCC along with strength properties were determined and compared with those of the OPC based SCC. Test results revealed that replacement of POFA in general decreased the workability of concrete with acceptable range. The compressive strength, however, increased with lower w/b ratio and lower replacement of ash. The splitting tensile and flexural strength values have also followed the same trend. The results obtained and the observation made in this study suggest that POFA can suitably be used as supplementary cementing material in SCC.